Synthesis and studies on chromene based reactive azo dyes and their applications on different fabrics - Badrey, Mohamed Gomaa; Gomha, Sobhi Mohamed; Mashaly, Hamada Moustafa (European Journal of Chemistry, 2016)
A number of reactive azo dyes based on chromene moiety were prepared through two inversed routes using 2-amino-7-hydroxy-4-phenyl-4H-chromene-3-carbonitrile, which when coupled to different diazonium salts, yielded the corresponding dyes which were then further reacted with cyanuric chloride. The structures of the prepared dyes were elucidated from their spectral data, elemental analyses and colour measurements. Dyeing of cellulosic and nylon fibers using the prepared dyes was done under suitable conditions. Some properties of the prepared dyes such as fastness properties (washing, rubbing and perspiration) and colour measurements were investigated. The dyes showed very good fastness to washing properties when attached to nylon fibers but poor fastness to light properties were shown.